Deciphering the task of N-acetyl aspartate in migraine. (September 2012) - Lionetto, Luana; Capi, Matilde; Vignaroli, Gabriele; Negro, Andrea; Martelletti, Paolo
Evaluation of: de Tommaso M, Ceci E, Pica C et al . Serum levels of N -acetyl-aspartate in migraine and tension-type headache. J. Headache Pain 13(5), 389–394 (2012). Migraine is a common neurological disorder producing significant personal and societal burden. In the evaluated study, serum concentrations of N -acetyl aspartate (NAA), a biomarker of neuronal integrity, was found to be decreased in patients suffering from migraine with aura. These interesting results suggest a dual clinical readout. Since migraine-with-aura patients show an increased risk for stroke; the evaluation of serum levels of NAA is crucial in the control of the conventional risk factors. In addition, the therapeutic metabolite monitoring of NAA may be helpful in the assessment of the chronicization process.